Determination of the Nutritional Habits and Anxiety Levels in Individuals with COVID-19 in Turkey - Iskender, Hatice; Dokumacioglu, Eda; Yalap, Osman (UI Scholars Hub, 2021)
Background: Coronavirus disease 2019 (COVID-19), which has spread worldwide since December 2019, has infected and claimed the lives of millions of people. This study aimed to investigate the relationship between anxiety levels and nutritional habits of patients with COVID-19. Methods: This cross-sectional study enrolled patients diagnosed with COVID-19 between February 1, 2021 and May 1, 2021. The study population included a total of 108 individuals with COVID-19 residing in Artvin, Turkey. This study used a self-administered online questionnaire, containing 40 questions from the State and Trait Anxiety Scale. Results: The state anxiety score was 37.26, and the trait anxiety score was 39.98. A strong, positive, and significant relationship was found between the state and trait anxiety levels of the participants (r = 0.588; p < 0.001). Conclusions: Many individuals who recovered from COVID-19 still suffer and struggle with the residual symptoms of COVID-19 for several months. Symptoms such as fatigue, weakness, pain, and malnutrition may occur even after recovery.